2011
DOI: 10.1111/j.1467-9507.2010.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Reactions to Toddlers' Negative Emotions and Child Negative Emotionality as Correlates of Problem Behavior at the Age of Three

Abstract: Parent-reported reactions to children's negative emotions and child negative emotionality were investigated as correlates of internalizing and externalizing behaviors. Children (N = 107) and their parents participated in a short-term longitudinal study of social development. Mothers and fathers independently completed questionnaires assessing parental reactions to their child's negative emotions and child negative emotionality at Time 1 (33 months) and child behavior problems at Time 2 (39 months).Child negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 67 publications
(123 reference statements)
2
31
0
1
Order By: Relevance
“…Studies have shown that fathers display more NSR to NE than mothers (Hughes & Gullone, 2010;McElwain et al, 2007;Wong et al, 2009), notably punitive and minimizing reactions (Eisenberg et al, 1996;Engle & McElwain, 2011;Cassano et al, 2007). As suggested by Engle and McElwain (2011), a higher level of paternal NSR may be due to the fact that fathers have fewer opportunities to respond to their children's NE than mothers. It could also be due to the different ways in which fathers and mothers interact with their children (Lamb & Lewis, 2004).…”
Section: Categorizationmentioning
confidence: 90%
See 1 more Smart Citation
“…Studies have shown that fathers display more NSR to NE than mothers (Hughes & Gullone, 2010;McElwain et al, 2007;Wong et al, 2009), notably punitive and minimizing reactions (Eisenberg et al, 1996;Engle & McElwain, 2011;Cassano et al, 2007). As suggested by Engle and McElwain (2011), a higher level of paternal NSR may be due to the fact that fathers have fewer opportunities to respond to their children's NE than mothers. It could also be due to the different ways in which fathers and mothers interact with their children (Lamb & Lewis, 2004).…”
Section: Categorizationmentioning
confidence: 90%
“…In terms of parents' characteristics, the literature singles out gender as a factor affecting emotion socialization behaviors (Cassano et al, 2007;Eisenberg et al, 1996;Engle & McElwain, 2011;Hughes & Gullone, 2010;McElwain et al, 2007;Wong et al, 2009). Studies have shown that fathers display more NSR to NE than mothers (Hughes & Gullone, 2010;McElwain et al, 2007;Wong et al, 2009), notably punitive and minimizing reactions (Eisenberg et al, 1996;Engle & McElwain, 2011;Cassano et al, 2007).…”
Section: Categorizationmentioning
confidence: 99%
“…However, we know little about the effects of ES on socio-emotional adjustment as a function of differences in children's emotional reactivity. The few available studies suggest that non-supportive ES responses predict behavior problems, particularly for preschoolers with emotional dysregulation (Hastings & De, 2008;Engle & McElwain, 2010).…”
Section: Role Of Child Emotionalitymentioning
confidence: 98%
“…Moreover, to explore the percentage of variance of parents' ERSBs explained by both parents' and children's characteristics, linear regression analyses by the stepwise method were applied. As in previous studies (e.g., [3] [26] [40]) having a moderate sample size, the use of multiple linear regression was evaluated as a good method in light of the objectives of the Study 1. Table 1 presents means and standard deviations for all measures and Table 2 presents inter-correlations between parental ERSBs, children's personality and parent's emotional competences.…”
Section: Discussionmentioning
confidence: 99%